Constructs Of Development From Inside The Development Communication Syllabi - Labor, Jonalou S. (Penerbit Universiti Sains Malaysia (USM Press), 2017)
Discourses of development in academic institutions must be thoroughly investigated. Using a set of Development Communication (DevCom) syllabi and the theories of Xu Xiaoge (2009) and Arturo Escobar (1995), this paper qualitatively investigated on the nature and process of the constructed discourse of development in an academic setting from sample course syllabi content, topics and activities. Results have shown that the syllabi's content and discourse are either pro-process or pro-participation development. Moreover, the set of studied syllabi have not actively articulated the post-development paradigm. The research suggests that faculty members who teach the course revisit the constructs of DevCom by constantly including development in the content, putting the discourse of alternatives to development, and theorising on the paradigm of development communication to further establish the feld.